A hollow-tube-like hydrospongel for multimodal therapy of advanced colorectal cancer - Tao Wu; Tenghui Li; Chengzhi Zhang; Yu Tian; Hao Li; Yuxin He; Xu Yan; Tianxing Gong; Junhua Zhao; Zhenning Wang (Nature Communications)
Abstract Preserving anal function in advanced-stage colorectal cancer (CRC) treatment remains a significant challenge. Here we introduce a hollow-tube-like hydrospongel (HTHSG) as an advanced neoadjuvant therapy. Constructed from cellulose nanofibers crosslinked with Fe3O4@PDA (polydopamine) nanoparticles, the HTHSG combines quick swelling (~10 seconds) with high fracture strength (>250 kPa) for enhanced mechanical stability. The hydrospongel enables precise, localized delivery of the chemotherapeutic agent 5-FU directly to the tumor site. Beyond conventional chemotherapy, HTHSG employs electromagnetic induction to achieve targeted thermal ablation and chemodynamic therapy, minimizing collateral damage to healthy tissues. Comparative studies in orthotopic, cell-derived, and patient-derived xenograft models demonstrate the superior tumor-reduction efficacy of HTHSG over traditional neoadjuvant therapies. Feasibility studies in a beagle model and human-sized dummy model further validate the HTHSG’s potential for clinical application, showing preserved anal function and biocompatibility. These findings establish HTHSG as a promising pre-surgical treatment option for advanced-stage CRC, offering improved therapeutic outcomes and quality of life for patients.